A novel Eu2+/Tb3+ co‐doped phosphor with pyroxene structure applied for cryogenic thermometric sensing. Issue 4 (17th December 2021) - Su, Ke; Guo, Qingfeng; Shuai, Pengfei; Liu, Ning; Mei, Lefu; Liao, Libing
Abstract: Pyroxene‐type phosphors were widely developed due to the advantages of high chemical stability, luminous efficiency, and low production cost. In this contribution, a series of Eu 2+ /Tb 3+ co‐doped Ca0.75 Sr0.2 Mg1.05 Si2 O6 (CSMS) phosphors with pyroxene structure were successfully synthesized by the solid‐state method. Under the 340 nm excitation, the emission peaks of the phosphor show a redshift with the increase of Eu 2+ concentration. The emitting color of Eu 2+ /Tb 3+ co‐doped samples shows a redshift attributed to the energy transfer from Eu 2+ to Tb 3+ . Simultaneously, acquired thermometer exposes superbly temperature‐sensitive properties ( S a and S r having maximum values 4.7% K −1 and 0.6% K −1, respectively) over the cryogenic temperature range (77–280 K). Furthermore, it has good stability and precision at cryogenic temperatures, indicating that CSMS:0.03Eu 2+ /0.03Tb 3+ phosphor is a very promising fluorescent material suitable for cryogenic temperature sensing. Abstract :